Effects of leaf maturity of piper sarmentosum (kaduk) on its antioxidant level - Ibrahim, Maizatul Akma; Azman, Sayidah Nafisah (2019)
Kaduk (Piper sarmentosum) is popular due to its culinary and medicinal properties and has been used traditionally in different parts of the world to cure many diseases and ailments. One of the studies which was conducted by Forest Research Institute of Malaysia (FRIM) shows that the extract from P. sarmentosum leaves contains antioxidant properties. However, a scientific study of its antioxidant level based on leaf maturity has not yet been conducted. Thus, this study aims to screen the antioxidant activity of P. sarmentosum based on the leaf maturity, from young, middle-age and matured leaves. The leaves were extracted by maceration using methanol and the antioxidant activity was determined by 1,1-diphenyl-2-picryl-hydrazyl (DPPH) assay. Results showed that the middle-age leaves contain the highest antioxidant activity followed by the young and matured leaves. Hence, if P. sarmentosum’s leaves are to be collected for its antioxidant properties, it is best to harvest the middle-age leaves to gain the optimized yield of antioxidant properties.